Volcanic Ash Deposition and Its Implications for Soil Biological Fertility: Insights from the Slopes of Mount Semeru, Indonesia - Tri Candra Setiawati; Rifky Putra Verdiawan; Lolita Endang Susilowati; Basuki; Saddam Matovani; Bambang Hermiyanto; Syahrul Efendi (Postgraduate, University of Mataram, 2026)
Volcanic ash from Mount Semeru can alter soil characteristics, including the biological properties. Microorganisms respond rapidly to changing environmental conditions, leading to the general consideration as sensitive indicators of soil health. In general, biological fertility status can be determined based on the Biological Fertility Index (BFI). Therefore, this study aims to assess the BFI and total population of soil microorganisms following the Mount Semeru eruption across four differently managed land-use systems, including monoculture and intercropping patterns. Field studies were conducted on the slopes of Mount Semeru, specifically in Pronojiwo Village, Lumajang Regency, at an elevation of 400-800 meters above sea level. The classification of the BFI was carried out through laboratory analysis of Soil Organic Matter (SOM), Microbial Biomass Carbon (MBC) by the fumigation extraction technique, Basal Soil Respiration (BSR), and Cumulative Soil Respiration (CSR) over a 25-day observation period, along with the total microbial population assessed using the agar plate method. The mineralization quotient (qCO2) and metabolic quotient (qM) were also calculated based on parameter measured. The results showed that BFI scores of 16.28 and 18.19 were obtained for monoculture and polyculture systems with volcanic ash cover exceeding 10 cm, showing an “intermediate” fertility status. In contrast, monoculture and polyculture land covered with volcanic ash <2 cm had BFI scores of 20.03 and 21.03, respectively, in the